HP24: Parieto-Premotor functional connectivity changes during parietal lobe seizures are associated with motor semiology. (March 2022) - Fonti, D.; Lagarde, S.; Pizzo, F.; Aboubakr, W.; Benar, C.; Giusano, B.; Puligheddu, M.; Bartolomei, F.
Abstract : Parietal lobe seizures (PLS) are characterized by multiple clinical manifestations including motor signs. The mechanisms underlying motor sings in PLS remains imperfectly known. The objective of this work was to understand this mechanism with the help of functional connectivity (FC) analysis. Method: We retrospectively selected patients affected by drug-resistant epilepsy who underwent Stereoelectroencephalography (SEEG) for pre-surgical evaluation and in whom the seizure onset zone (SOZ) was located in the parietal cortex. The SOZ was defined visually and quantitatively by the epileptogenicity index (EI) method (Bartolomei F et al. Brain 2008; 131: 1818–1830.) Two groups of seizures were defined according to the presence ("motor seizures") or the absence ("non-motor seizures") of motor signs. FC estimation was based on pairwise nonlinear regression analysis (h 2 coefficient). For studying the FC changes between parietal, frontal and temporal regions, for each patient, z-score values of 16 cortico-cortical interactions have been obtained comparing h 2 coefficients of pre-ictal, seizure onset and seizure propagation periods. Result: We included 22 patients, 13 with "motor seizures" and 9 with "non-motor seizures". Z scores computed between the onset and the propagation of discharges were significantly higher in "motor seizures", between lateral pre motor area and precuneus (p = 0, 01), lateral pre motor area and superior parietal lobule (p = 0.03) and between inferior parietal lobule/posterior cingular gyrus and supplementary motor area (SMA)(p = 0.04). Conclusions: Our study shows that motor semiology in PLS are underline by an increase of FC between parietal and premotor cortices, significantly different than what is observed in PLS without motor semiology.